Simulation of Voltammogram of a Hindered Quinomethylene (Biological Sciences - PJSIR, 2006)
Electrochemical simulation of the cyclic voltammogram of a sterically hindered quinomethylene in dimethyl formamide (DMF) tetra-n-butylammonium perchlorate at mercury bead electrode was studied using two shareware simu- lation programs, namely, cyclic voltammetry simulation (CVSIM) and Electrochemical simulation package 2.4 (ESP 2.4). Two cathodic and two anodic peaks were analysed. ESP 2.4 took lesser time for simulations.